High salinity enhances the adsorption of 17α-ethinyl estradiol by polyethersulfone membrane: isotherm modelling and molecular simulation - Goh, J. Y. (2022)
The increasing occurrence of steroidal hormone micropollutant in the aquatic environment and their associated consequences have caused serious environmental concerns globally. Adsorptive removal of hormonal pollutants using polymeric membranes has been suggested but information on their performance in various environmental conditions is lacking. In this study, we examined the effect of salinity on the performance of polyethersulfone (PES) membrane to remove synthetic hormone 17α-ethinyl estradiol (EE2) from water. Our results show that an increase of salinity from 0 to 3% results in higher retention of EE2 onto PES membrane from 79.3 to 98.7%. The experimental results fit the Freundlich isotherm model better as compared to the Langmuir model. The Freundlich parameters n and Kf yielded the highest values at 3% salinity. The molecular simulation results suggest that a high salinity increases the binding energy between EE2 and PES membranes, promoting the PES-EE2 interaction through π–π interaction, hydrogen bonding and hydrophobic interaction. This study provides valuable information for improving design of specialised treatment facilities (in farming, pharmaceutical industries, etc.) to allow better removal of EE2 and other low-polar organic contaminants from water via a membrane-based sorption-elution method, and we recommend the inclusion of salinity as a factor in modelling the adsorption capacity of membranes to prevent the oversaturation of membrane and minimise the release of contaminants into the environment.